Hustle Culture: Celah Pelanggaran terhadap Hukum Ketenagakerjaan - Ellen Lutya Putri Nugrahani; Jody Imam Rafsanjani; Zaihan Harmaen Anggayudha; Hilmi Ardani Nasution (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2025)
Hustle Culture promotes hard work and exceeding standard working hours as a pathway to career success. However, it is often exploited to justify practices that violate labor laws, such as forcing employees to work beyond regulated hours without fair overtime pay or compensation. While seen as a driver of productivity, Hustle Culture risks undermining workers' rights and well-being. This article examines how companies misuse Hustle Culture to manipulate employees into working excessively, potentially breaching labor laws. It also explores the balance between hard work and the protection of workers' rights, emphasizing the need for healthy and sustainable work environments. Using a normative method with a qualitative descriptive approach, the study analyzes relevant legal documents. Findings indicate that Hustle Culture can be weaponized by employers to coerce excessive labor, disregarding the negative impacts on workers' physical and mental health. Such practices not only harm employee welfare but also risk violating labor laws on working hours and overtime pay. This research highlights the importance of aligning workplace expectations with legal protections to ensure fair treatment and long-term sustainability in professional environments.